BCI-IOT - prof. Mrs. Manjula k; Sharath VN (International Journal of Innovations in Engineering Research and Technology, 2021)
With theadvancement in technology, the mode of interaction with the electrical devices has also advanced. This paper proposes a brain computer interface BCI for regulating everyday house hold appliances ranging from a simple mechanical switchbased control of electrical devices to IoT based wireless control facility. This technology includes an EEG device to acquire signals associated to the brain activity and communication protocol. The integration of BCI and IoT for “CONTOLLING THE THINGS REMOTELY” is a promising and emerging technique to make home environment comfortable by easy access, automation and optimization of home appliances such as television sets, ac light bulbs and so on. In addition to this, monitoring brain activity in real time through cloud server a major role in education and medical fields to monitor the concentration and attention levels of students and to monitor brain activity of patients in coma respectively.